The Giant Post-Traumatic Diaphragmatic Hernia: Clinical Case and Literature Review - S. A. Domrachev; S. A. Kucher (Неотложная медицинская помощь)
The post-traumatic diaphragmatic hernia is a rare type of trauma which most commonly occurs after the blunt trauma of the thorax and abdomen. In the acute period of trauma, the symptoms of the emergency diseases and nonspecific signs of the diaphragmatic rupture are the reasons of frequent diagnostic mistakes. A missed diaphragmatic rupture grows in time and leads to migration of organs from the abdominal cavity to the thoracic one due to pressure gradient. The symptoms of diaphragmatic hernia are not expressed and the duration of the asymptomatic period of the disease may vary from some years to 10 years and longer. The increasing restructuring of the abdominal wall leads to reduced abdominal cavity, which makes the standard reconstructive surgery difficult, the intraabdominal pressure grows and relapse occurs in the postoperative period. In these cases, surgeons perform complex techniques which enlarge the abdominal cavity with local tissues or an artificial graft. However, there are no clear recommendations about the extent of the abdominal wall reconstruction so that the abdominal cavity size would be adequate for organs. The authors suggested a simple method to calculate it and used it in practice. In the article, we report the clinical case of a 53-year-old woman with a giant post-traumatic diaphragmatic hernia after motor vehicle accident 48 years ago and offer an original method of treatment. The first operation including hernia resolution and repair of diaphragmatic rupture was complicated by relapse on the second day after operation due to the high intra-abdominal pressure. During the second reconstructive surgery (4 months later), the authors performed their own method of abdominal cavity enlargement and got a good result in the shortand long-term postoperative period.